2022
DOI: 10.1158/1055-9965.epi-21-0463
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Pathology Features of Colorectal Tumors and Patient Outcomes Are Associated with Fusobacterium nucleatum and Its Subspecies animalis

Abstract: Background: Fusobacterium nucleatum (F. nucleatum) activates oncogenic signaling pathways and induces inflammation to promote colorectal carcinogenesis. Methods: We characterized F. nucleatum and its subspecies in colorectal tumors and examined associations with tumor characteristics and colorectal cancer–specific survival. We conducted deep sequencing of nusA, nusG, and bacterial 16s rRNA genes in tumors from 1,994 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…The microbial subtypes were associated with distinct prognosis and clinical patient phenotypes such as staging, tumour location, history, lymphovascular invasion and TP53 status. Interestingly, we did not observe an association between the microbial subtypes with microsatellite instability, CMS-[39] and CRIS-[40] subtypes, despite observing such a relationship with individual families, particularly Bacteroidaceae and Fusobacteriaceae, as previously reported [11,33,42]. These findings further underscore the orthogonal value of microbial fingerprinting in addition to transcriptomic-based subtyping and more conventional stratification signatures and clinical markers.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The microbial subtypes were associated with distinct prognosis and clinical patient phenotypes such as staging, tumour location, history, lymphovascular invasion and TP53 status. Interestingly, we did not observe an association between the microbial subtypes with microsatellite instability, CMS-[39] and CRIS-[40] subtypes, despite observing such a relationship with individual families, particularly Bacteroidaceae and Fusobacteriaceae, as previously reported [11,33,42]. These findings further underscore the orthogonal value of microbial fingerprinting in addition to transcriptomic-based subtyping and more conventional stratification signatures and clinical markers.…”
Section: Discussionsupporting
confidence: 67%
“…On-tumour tissue was enriched with Fusobacteria , Proteobacteria , Basidyomicota and depleted of Bacteroidetes , Firmicutes , Ascomycota compared with adjacent off-tumour mucosa. Abundance of Fusobacteria , largely from the Fusobacteriaceae family and Fusobacterium nucleatum species, have been implicated in the aetiology [12,31,41], clinical phenotype [11,33,34,42] such as tumour location, microsatellite instability, assignment to transcriptome-based molecular subtyping, clinico-pathological features, therapy response [32,43] and, ultimately, clinical outcome [11,33,44]. This study identified a depletion of Firmicutes, driven by Clostridia, but not Bacilli, and Bacteroidetes, driven by Bacteroidia, but not Flavobacteriia, corroborating findings in the CRC settings [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nucleatum ( Fnn ), animalis ( Fna ), polymorphum ( Fnp ), vincentii/fusiforme ( Fnv ) 24,25 . Fna is the most prevalent subspecies found in CRC in epidemiological studies 26,27 , and we therefore sampled Fna at a higher frequency (10/14 isolates tested). We confirmed that 5-FU is a potent growth inhibitor of CRC Fn isolates representing all four subspecies, suggesting that 5-FU sensitivity is a core feature of Fn species (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…CRC containing F. nucleatum is characterised by proximal tumour localisation, BRAF mutation, high-level microsatellite instability, high-level CpG island methylator phenotype,27–29 decreased CD3 + CD4 + CD45RO (PTPRC) + cells30 and increased tumour-associated macrophages 31. Specifically, F. nucleatum subspecies animalis may play a role in most of these associations 32…”
Section: Tumour Microenvironmentmentioning
confidence: 99%